Proficiency-based progression training: implementing a novel approach to training for epidural analgesia in labour. (November 2021) - Mohamed, H.; McAuliffe, N.; O'Connor, R.; Ceballos Salazar, A.; Zohaib Aslam, M.; Kallidaikurichi Srinivasan, K.; Iohom, G.; Shorten, G.
Highlights: Epidural catheter placement is among the most challenging procedural skills. Proficiency-based Progression (PbP) resulted in a 12% epidural failure rate. PbP training implementation is feasible for meaningful patient outcomes. PbP training is associated with high patient satisfaction. Abstract: Background: Epidural insertion is a challenging anaesthetic procedural skill to learn and may require up to 75 attempts to achieve competency. Proficiency-based progression (PbP) training based on unambiguously defined metrics was associated with a 53% reduction in epidural failure rate. The aim of this observational study was to examine the feasibility of implementation of innovative PbP training for labour epidural insertion performed by novices in a busy tertiary hospital. Methods: All trainees who were scheduled to commence their obstetric anaesthesia training were invited to participate. Novices undertook intensive PbP training with one-to-one supervision by an anaesthetist trained in PbP. Trainees proceeded to the clinical phase only after attaining the pre-defined proficiency benchmark. All subsequent attempts at labour epidural catheter placement were evaluated. Results: All 12 novice trainees who were scheduled for their initial exposure to obstetric anaesthesia completed PbP training in epidural catheter insertion successfully. The average duration of the training courses was 70 (SD 11) min. Trainee characteristics were broadly similar. They performed a total of 180 labour epidural catheter placements with an overall epidural failure rate of 12.2% (22/180). The proportion of supervisor takeover was 6% (11/179). The incidence of complications was 4% (8/180) and difficulty in epidural catheter insertion due to patient factors was 16% (29/180). Patient satisfaction rates were 80% (satisfied or very satisfied), with 20% unsatisfied with their experience of epidural insertion. Conclusion: In our experience, PbP training in epidural placement is feasible within existing departmental resources in a busy tertiary teaching hospital setting.